High on Hookah: Smoking Marijuana from a Hookah among Adults in the United States, Population Assessment of Tobacco and Health Study, 2015–2019. (16th April 2023) - Ebrahimi Kalan, Mohammad; Jebai, Rime; Li, Wei; Gautam, Prem; Osibogun, Olatokunbo; Alqahtani, Mohammed M.; Ward, Kenneth D; Behaleh, Raed; Bursac, Zoran; Ben Taleb, Ziyad
Abstract: Background: This study aimed to examine the trend and factors associated with smoking marijuana from a hookah device among US adults. Methods: Data were drawn from the Population Assessment of Tobacco and Health (PATH) Study, an ongoing nationally representative, longitudinal cohort study of the US population. Adult respondents who self-reported ever smoking marijuana from a hookah at Wave 5 (2018–19, N = 34, 279 US adults) were included in the multivariable analysis. Trend analysis also was conducted using National Cancer Institute JoinPoint software from 2015 to 2019. Results: In 2018–19, an estimated 23.6 million (9.7%) US adults reported ever smoking marijuana from a hookah. Trend analysis showed the increasing prevalence of using marijuana from a hookah device from Wave 3 (8.9%) to Wave 5 (9.7%; time trend p = .007). Adults aged 25–44 years old (vs. 18–24; 13%, vs. 9%), whites (vs. Black; 11% vs. 9%), and lesbian, gay, or bisexual (LGB vs. straight; 17% vs. 9%) were more likely to report ever smoking marijuana from a hookah ( ps < .05 ). Former and current users (vs. never users) of e-cigarettes (19% and 25% vs. 5%), cigarettes (11% and 21% vs. 2%), cigars (17% and 27% vs. 3%), and pipes (21% and 33% vs. 7%) and past 30-day blunt users (vs. non-users; 39% vs. 9%) were more likely to ever smoke marijuana from a hookah ( ps < .05 ). Pregnant women (vs. non-pregnant; 12.8% vs. 8.6%; p = 0.03) were more likely to smoke marijuana from a hookah. Conclusions: Smoking marijuana from a hookah device is prevalent among young adults in the US, especially among vulnerable populations, and has increased significantly from 2015–2019.